Bidirectional regulation of the cGAS-STING pathway in the immunosuppressive tumor microenvironment and its association with immunotherapy - Zhang, Yurui; Wang, Yudi; Mu, Peizheng; Zhu, Xiao; Dong, Yucui (Frontiers in Immunology, 2024)
Adaptive anti-tumor immunity is currently dependent on the natural immune system of the body. The emergence of tumor immunotherapy has improved prognosis and prolonged the survival cycle of patients. Current mainstream immunotherapies, including immune checkpoint blockade, chimeric antigen receptor T-cell immunotherapy, and monoclonal antibody therapy, are linked to natural immunity.The cGAS-STING pathway is an important natural immunity signaling pathway that plays an important role in fighting against the invasion of foreign pathogens and maintaining the homeostasis of the organism. Increasing evidence suggests that the cGAS-STING pathway plays a key role in tumor immunity, and the combination of STING-related agonists can significantly enhance the efficacy of immunotherapy and reduce the emergence of immunotherapeutic resistance. However, the cGAS-STING pathway is a double-edged sword, and its activation can enhance anti-tumor immunity and immunosuppression. Immunosuppressive cells, including M2 macrophages, MDSC, and regulatory T cells, in the tumor microenvironment play a crucial role in tumor escape, thereby affecting the immunotherapy effect. The cGAS-STING signaling pathway can bi-directionally regulate this group of immunosuppressive cells, and targeting this pathway can affect the function of immunosuppressive cells, providing new ideas for immunotherapy. In this study, we summarize the activation pathway of the cGAS-STING pathway and its immunological function and elaborate on the key role of this pathway in immune escape mediated by the tumor immunosuppressive microenvironment. Finally, we summarize the mainstream immunotherapeutic approaches related to this pathway and explore ways to improve them, thereby providing guidelines for further clinical services.